Sustainable development of chitosan-gelatin composite films for food packaging using crude chitosan extracted from American lobster (Homarus americanus) shell waste - Abhinav Jain; Beth Mason; Marianne Su-Ling Brooks (Carbohydrate Polymer Technologies and Applications)
In this study, crude chitosan extracted from American lobster shells (Homarus americanus) was used to develop bio-based films. These films were prepared using solvent casting at various drying temperatures (37, 60, and 80 °C) and enhanced by blending with sunflower oil and gelatin from fish skin. Structural and thermal analyses (FT-IR, XRD, and TGA) demonstrated excellent compatibility between the extracted chitosan and fish gelatin. A 1:1 blend of these biopolymers resulted in films with increased flexibility and reduced water vapor permeation compared to pure chitosan films. Adding 10 % (w/w polymer) sunflower oil improved surface hydrophobicity and reduced swelling without compromising strength. Higher drying temperatures increased swelling, stretchability, and opacity, but decreased tensile strength and vapor permeability. Films prepared at 80 °C exhibited the best elasticity (100.4 %) and the lowest vapor permeability (1.2 g.mm/kPa.h.m2) while maintaining adequate tensile strength (27 MPa). This study demonstrates a sustainable approach for developing chitosan-gelatin composite films using renewable marine processing byproducts. In particular, the applicability of crude chitosan extracted from waste lobster shells (without additional purification steps) as a cost-effective and sustainable feedstock is highlighted, offering an eco-friendly alternative to conventional plastic food packaging.